Prototype of running clinical trials in an untrustworthy environment using blockchain - Daniel R. Wong (Nature Portfolio, 2019)
Ensuring the integrity of clinical trial data is crucial to securing trust in the process. Here, the authors present a prototype of a blockchain-based clinical trial management system that ensures immutability and traceability of trial data, and demonstrate a proof of concept web portal service.